2011
DOI: 10.1007/s00405-011-1749-x
|View full text |Cite
|
Sign up to set email alerts
|

Deep inferior epigastric artery perforated rectus abdominis free flap for head and neck reconstruction

Abstract: The deep inferior epigastric artery perforated rectus abdominis (DIEAP-ra) free flap is a modification of the classic myocutaneous DIEA free flap in which only fasciocutaneous tissue is harvested based on the paraumbilical perforators of the medial row. The aim of this retrospective study is to describe our experience with this reconstructive technique in head and neck surgery. Between 2004 and 2009, 24 patients affected by oncologic maxillofacial, skull base, oral, and oropharyngeal defects were submitted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…[9][10][11] The DIEAP flap provides adequate flap bulk and is suitable for large three-dimensional reconstructions of craniofacial defects involving orbits and maxillas. 12,13 The TAP flap may provide a large flap volume and a long pedicle, 14 and our experience showed that it is suitable for reconstructions of cranial bone defects with large areas of scalp defects. However, the patient may need to change position during the surgery.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…[9][10][11] The DIEAP flap provides adequate flap bulk and is suitable for large three-dimensional reconstructions of craniofacial defects involving orbits and maxillas. 12,13 The TAP flap may provide a large flap volume and a long pedicle, 14 and our experience showed that it is suitable for reconstructions of cranial bone defects with large areas of scalp defects. However, the patient may need to change position during the surgery.…”
Section: Discussionmentioning
confidence: 84%
“…A variable amount of the vastus lateralis muscle can be included with the fascia and skin components of the flap for deep defects requiring bulk to restore the craniofacial contour or defects in which dural or other critical neurovascular structures need coverage . The DIEAP flap provides adequate flap bulk and is suitable for large three‐dimensional reconstructions of craniofacial defects involving orbits and maxillas . The TAP flap may provide a large flap volume and a long pedicle, and our experience showed that it is suitable for reconstructions of cranial bone defects with large areas of scalp defects.…”
Section: Discussionmentioning
confidence: 91%
“…Although DSS an OS are low due to loco-regional recurrence or distant metastases in total or subtotal glossectomy and despite we did not performed a quality of life assessment, the patients reconstructed with a vertical rectus abdominis muscle flap referred an improvement in the quality of life following reconstruction. Functional rehabilitation remains difficult but the use of the myocutaneous free flap has been demonstrated to deliver good outcomes [18]. In our series, the vertical rectus abdominis muscle flap was fixed anteriorly to the mandible and posteriorly to the base of tongue.…”
Section: Discussionmentioning
confidence: 94%
“…When large amounts of muscles are harvested, donor site morbidity is increased and therefore, it is our opinion that other free tissue donor sites offer several advantages over the rectus abdominis flap in the majority of cases. Muscle sparing perforator style flaps may allow for decreased morbidity and superior control of flap thickness, and the deep inferior epigastria artery-based flaps have been shown to be a valid reliable option for head and neck reconstruction [26]. …”
Section: Reconstructive Managementmentioning
confidence: 99%